The Fighting Kentuckian - Waggner, George, 1894-1984; Wayne, John, 1907-1979; Miles, Vera; Hardy, Oliver, 1892-1957; Dorn, Philip, 1905-1975; Copyright Collection (Library of Congress) (United States : Republic Pictures, 1949)
While on their way home after fighting with General Andrew Jackson at New Orleans, two Kentucky riflemen, John Breen and Willie Paine, stop in a French colony in Alabama. Breen falls in love with Fleurette DeMarchand. He and Paine stay to help her family and the rest of the colonists who are trying to save their land from some rascals who are trying to cheat them.
Copyright: Republic Pictures Corp.; 9Sep49; LP2570.
Minor change version: [Colorized version]. -- United States : [Republic Pictures], 1990.
Copyright for minor change version: Republic Pictures Corporation. Prev. reg.: 1949, LP2590; renewed R389260. NM : colorization. DCR 1990; PUB 15Jan90; REG 7Oct93; PA741- 749.
Source used: M/B/RS Descriptions file.
John Wayne, Vera Ralston, Oliver Hardy, Philip Dorn, Marie Windsor, John Howard, Hugo Haas, Grant Withers, Odette Myrtil, Mae Marsh.
Keywords: United States. -- Army. -- Cavalry -- Drama; Immigrants -- Alabama -- Drama; French -- Alabama -- Drama; Soldiers -- Kentucky -- Drama; Adventure films; United States -- History -- 1809-1817 -- Drama; Features; Historical re-creations.